Policies and obligation of women athletes clothing at international sports events: A literature study - Agustina, Dina; Rismayanthi, Cerika; Sumaryanti, Sumaryanti; Yuniana, Rina; Nugroho, Sigit; Haidar, Muhammad Daffa; Wang, Ziyu; Murgolo, Michael (Universitas Tanjungpura, 2024)
Background and Study Aim. The participation of female athletes in a sporting event in each country is very minimal compared to men, basically the State policy has not fully allowed female athletes to wear the hijab. Hijab is familiar to Muslim women but on the other hand the policies of their respective countries do not support Muslim women participating in a sporting event by wearing hijab. This study aims to explore the involvement of Muslim women who wear hijab in international sporting eventsMaterial and Methods. This research used Harzing Publish or Perish to start the search, Scopus database was used, which is considered as one of the best citation indexing tools. The criteria used the PRISMA protocol (preferred reporting items for systematic reviews and meta-analyses). The keywords of this research are (